Comparison of the efficacy and safety of perioperative immunochemotherapeutic strategies for locally advanced esophageal cancer: a systematic review and network meta-analysis - Zhang, Jiao; Zhao, Peixi; Xu, Rui; Han, Le; Chen, Wenjuan; Zhang, Yili (Frontiers in Immunology, 2024)
BackgroundThe aim of this network meta-analysis was to clarify the efficacy and safety of different immune checkpoint inhibitors (ICIs) in combination with chemotherapy in the neoadjuvant phase for the treatment of locally advanced esophageal cancer.MethodsWe searched PubMed, EMBASE, Web of Science, Cochrane Library, CNKI and WanFang databases from January 2000 until May 2024. The primary endpoints were pathological complete response (pCR), major pathological response (MPR), R0 resection rate, objective response rate (ORR), disease control rate (DCR), treatment-related adverse events(TRAEs) of any grade and TRAEs of grade 3 or higher. The Newcastle-Ottawa Scale (NOS) and the Cochrane Risk of Bias tool were used to evaluate risk of bias. To analyze the data, Review Manager 5.3 and Stata16.0 were applied.ResultsFourteen eligible studies (six randomized controlled trials) and 8 retrospective cohort studies) enrolling 1139 patients were included for this network meta-analysis. All studies originated from China. For patients with locally advanced esophageal cancer, neoadjuvant immunochemotherapeutic strategies showed significant advantages over traditional neoadjuvant therapy in terms of pCR, MPR, ORR and DCR. Among the analyzed regimens, camrelizumab plus chemotherapy demonstrated the most pronounced improvements in pCR and MPR, while pembrolizumab plus chemotherapy achieved the best outcomes in terms of ORR and DCR. There were no significant differences observed among the various neoadjuvant treatment strategies regarding R0 resection rate, any grade TRAEs, or grade≥3 TRAEs. The most common TRAEs in the neoadjuvant chemotherapy plus immunotherapy group were myelosuppression and gastrointestinal damage, with most grade 3 or higher TRAEs being hematologic adverse events. The most frequent immune-related adverse events(irAEs) included rash (4.2-21.7%), thyroid dysfunction (hypothyroidism or hyperthyroidism, 6.3-17.4%), and pneumonia (4.2-6.3%), with the majority being mild to moderate (grade 1 or 2).ConclusionsNeoadjuvant immunotherapy combined with chemotherapy regimens demonstrate relatively high efficacy and tolerable safety profiles. Among the evaluated regimens, the combination chemotherapy with camrelizumab had relatively high pCR and MPR, whereas the combination chemotherapy with pembrolizumab had relatively high ORR and DCR. There were no significant differences in safety among the various regimens. Our study suggests that evaluating the efficacy and safety of different ICIs may be helpful in clinical decision-making.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024583548.